The Crime of Passive Bribery in Indonesia: A Comparison with Several Countries - ., Nurwinardi; Suwadi, Pujiyono; ., Hartiwiningsih (Journal of Ecohumanism, 2025)
This research aims to describe the form of regulation of the crime of passive bribery in countries such as the Netherlands, Malaysia and China. This is done because it sees the form of regulation of the criminal offence of passive bribery in Indonesia which experiences dualism of regulation, namely in Article 5 Paragraph (2) and Article 12 letter a of Law Number 20 of 2001 concerning Corruption. This research is a normative legal research with a comparative legal approach. The results of the research show that looking at the arrangements of countries such as Malaysia, the Netherlands, and China. These countries have various forms of regulation regarding the crime of passive bribery, there are countries that regulate in special rules and are included in the legal regime of corruption crimes such as Malaysia. However, there are also countries that include it in the general rules in the Criminal Code of each country such as the Netherlands and China. However, regardless of the regulatory model, the most substantial is the certainty of each country in formulating offences and providing sanctions that are not regulated in two different provisions (legal dualism).